Environmental, resident and bystander exposure from spraying applications with unmanned aerial vehicles equipped with flat-fan nozzles or rotary atomizers - Pierre-Henri Dubuis; Céline Villars-Corbex; M. Clare Butler Ellis; H. Christoph Geiser; Jeremy J. Harwood; Marco C. Knobloch; Andrew G. Lane; Aurélie Melgar; Joel D. Stohler; Clive R. Tuck; Helen C. Wheeler; Jürg A. Zarn; et al. (Crop Protection, 2026)

Dynamics of nitrogenase cofactor elements and resource limitation of asymbiotic biological nitrogen-fixation during long-term pedogenesis - O. M. Butler; G. Liang; S. Matsumura; C. R. Chen; B. Kaiser; C. R. Warren (Plant and Soil, 2026)
Background and aims Biological nitrogen fixation (BNF) is central to long-term pedogenesis and overall terrestrial ecosystem development. Rates of asymbiotic BNF are potentially constrained by carbon (C), phosphorus (P), and/or nitrogenase cofactor elements (e.g., iron [Fe], vanadium [V], and molybdenum [Mo]), but our understanding of the biogeochemical trajectories of cofactor elements throughout pedogenesis is limited. Methods Using a ~ 700 ka pedogenic chronosequence at Cooloola in eastern Australia, we quantified P, Fe, V, and Mo in soil and litter and tested for C (i.e., energy), P, and/or Mo limitation of asymbiotic BNF using acetylene reduction assays. Results Cofactor elements in soil declined faster than P during pedogenesis, and their relative extractability with chelating agents increased across the chronosequence. Addition of C, P, and/or Mo did not affect asymbiotic BNF in any dune system tested. Conclusion Declines of soil P and cofactor elements during pedogenesis support an underlying influence of weathering on the biogeochemical cycling of these elements. However, dynamics of Fe, V, and Mo diverge from those of P due to increasing chelation by SOM as podzolization advances, whereas P is increasingly present in organic forms. Asymbiotic BNF is seemingly not limited by C, P, or Mo during pedogenesis at Cooloola.

Lace monitors scavenge the large carcass of an endangered eastern freshwater cod - Brendan C. Ebner; John St Vincent Welch; Leo M. Cameron; Jason Schaffer; Gavin L. Butler (Food Webs, 2026)

Microbial phosphorus in loamy, basalt-derived forest soil is altered by plant nutritional status: a root-splitting study - O. M. Butler; C. R. Warren (Plant and Soil, 2025)
Background and aims Soil nutrient content is a major driver of primary productivity. Microbial biomass comprises a substantial soil nutrient pool, the properties of which could be shaped by plant nutrient-limitation status. We aimed to determine how plant nutrition affects soil microbial biomass nitrogen (MBN) and phosphorus (MBP), and whether such effects are linked to microbial composition. Methods To isolate the effect of plant nutrition on soil microbes, we used a split-root system with Syncarpia glomulifera Smith seedlings fertilised with either P-free Hoagland solution or a P-only solution, and quantified rhizosphere soil microbial biomass carbon (MBC), MBN, MBP, and microbial polar lipid fatty acids (PLFAs). Results Provision of N + micronutrients to S. glomulifera seedlings in basalt-derived soils led to a 19% decline in soil MBP relative to controls. This effect was not evident in comparatively P-depleted sandstone-derived soils. MBC and MBN were not affected by plant nutritional status, and neither were the abundances and composition of microbial PLFAs. Conclusion Rhizosphere microbial nutrient pools are potentially sensitive to plant nutritional status. Microbial P can be reduced when plants are P-limited. These effects are not necessarily paralleled by altered microbial composition, implicating microbial physiology as a possible driver of variation in microbial P.

Phenology and yield do not scale from single row to whole plot in chickpea and lentil - L. Lake; R. Gimenez; R. Ortega Martinez; J. L. Weller; M. Javid; J. B. Butler; L. E. James; M. F. Dreccer; R. French; C. M. Cossani; J. E. Hayes; V. O. Sadras (Euphytica, 2025)
Reliable phenotyping is critical for pre-breeding and breeding. Some traits such as herbicide tolerance are more likely to scale from plant to crop than others such as yield. Here we compared phenology, yield and its components in two arrangements—single rows and whole plots—for 10 chickpea and 10 lentil cultivars in 11 (chickpea) and 10 (lentil) Australian environments resulting from the combination of location, season, and sowing date. The cultivars were characterised for key genetic loci for phenology: Elf3a , GI and the FT gene cluster in chickpea, and GWAS-chr2 and the FTb gene cluster in lentil. Across environments, yield of chickpea ranged from 33 to 268 g per lineal m (g m −1 ) in single rows and 5 to 77 g m −1 in whole plots, and yield of lentil ranged from 20 to 174 g m −1 in single rows and 9 to 104 g m −1 in whole plots. Across environments and genotypes, time to flowering was later in 207 of 275 chickpea whole plots compared with single rows and in 175 out of 234 lentil whole plots compared with single rows. In both chickpea and lentil, flowering and podding varied with the interaction between genotype, arrangement, and environment, resulting in altered genotypic rankings between single row and whole plot within and between environments. Yield components were variably affected by the three-way interaction; biomass was the only trait showing no interaction in either crop. Broad sense heritability of seed size fell from 0.60 in whole plots to 0.37 in single rows for chickpea, and from 0.87 to 0.62 in lentil. We highlight the need to understand scaling for agronomically important traits to avoid wasteful or counterproductive phenotyping and breeding efforts.

Acute and vicarious effects of social defeat stress on social behaviour in California mice, Peromyscus californicus - Hanna M. Butler-Struben; Alexis M. Black; Sophia M. Wright; Alicia F. Dye; Brian C. Trainor (Animal Behaviour, 2025)

Time-lapse resistivity imaging and self-potential monitoring of experimentally induced saline intrusion in coastal aquifer sands - Jesús F. Águila; Thomas S.L. Rowan; Mark C. McDonnell; Raymond Flynn; Shane Donohue; Matthew D. Jackson; Adrian P. Butler; Gerard A. Hamill; Eric M. Benner; Georgios Etsias (Science of The Total Environment, 2025)

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Corrigendum: Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2025)

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The diversity, distribution, and temporal stability of coral ‘zooxanthellae’ on a pacific reef: from the scale of individual colonies to across the host community - Allison M. Lewis; Caleb C. Butler; Kira E. Turnham; Drew F. Wham; Kenneth D. Hoadley; Robin T. Smith; Dustin W. Kemp; Mark E. Warner; Todd C. LaJeunesse (Coral Reefs, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Complementary and Inducible creERT2 Mouse Models for Functional Evaluation of Endothelial Cell Subtypes in the Bone Marrow - Michael G. Poulos; Pradeep Ramalingam; Agatha Winiarski; Michael C. Gutkin; Lizabeth Katsnelson; Cody Carter; Laurence Pibouin-Fragner; Anne Eichmann; Jean-Leon Thomas; Lucile Miquerol; Jason M. Butler (Stem Cell Reviews and Reports, 2024)
In the adult bone marrow (BM), endothelial cells (ECs) are an integral component of the hematopoietic stem cell (HSC)-supportive niche, which modulates HSC activity by producing secreted and membrane-bound paracrine signals. Within the BM, distinct vascular arteriole, transitional, and sinusoidal EC subtypes display unique paracrine expression profiles and create anatomically-discrete microenvironments. However, the relative contributions of vascular endothelial subtypes in supporting hematopoiesis is unclear. Moreover, constitutive expression and off-target activity of currently available endothelial-specific and endothelial-subtype-specific murine cre lines potentially confound data analysis and interpretation. To address this, we describe two tamoxifen-inducible cre -expressing lines, Vegfr3-creER T2 and Cx40-creER T2 , that efficiently label sinusoidal/transitional and arteriole endothelium respectively in adult marrow, without off-target activity in hematopoietic or perivascular cells. Utilizing an established mouse model in which cre -dependent recombination constitutively-activates MAPK signaling within adult endothelium, we identify arteriole ECs as the driver of MAPK-mediated hematopoietic dysfunction. These results define complementary tamoxifen-inducible creER T2 -expressing mouse lines that label functionally-discrete and non-overlapping sinusoidal/transitional and arteriole EC populations in the adult BM, providing a robust toolset to investigate the differential contributions of vascular subtypes in maintaining hematopoietic homeostasis. Graphical Abstract

Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2024)
That coral reefs are in decline worldwide, particularly in the Caribbean, will come as no surprise. This decades-long decline has reached a potential tipping point as the weight of the effects of climate change have come decidedly to bear on the planet’s most diverse marine ecosystem. Whether coral reefs can persist without restorative intervention is debatable, which has prompted a surge in coral reef restoration projects focusing primarily on the cultivation and transplantation of coral fragments onto degraded reefs. But that widespread approach does little to address the underlying causes of coral loss, one of which is the proliferation of macroalgae that are deleterious to corals. An emerging solution to this problem is the enhancement of herbivory on coral reefs through improved management of herbivores, artificial enhancement of herbivore settlement, or their mariculture and subsequent stocking. This review explores the nuances of the biology of well-studied Caribbean coral reef herbivores (fishes, sea urchins, and crabs) as it relates to their mariculture and investigates the promise of herbivore stocking onto coral reefs as a restoration strategy. Fish, urchin, and crab herbivores differ appreciably in life histories, which confers advantages and disadvantages with respect to their mariculture and effectiveness as grazers. Mariculture of herbivorous marine fish for reef restoration is essentially non-existent so the reestablishment of grazing fish abundance on coral reefs focuses primarily on their protection through fishery regulations, but only at a few locations in the Caribbean. Mariculture of herbivorous urchins and crabs for restoration purposes is in its infancy, but promising especially for crabs whose larval rearing is less difficult. Perhaps the biggest challenge for the mariculture of either taxon is “scaling-up” from research settings to large-scale mariculture needed for stocking. Numerous studies extol the benefits of functional redundancy and complementarity for coral reef ecosystem stability, but whether this principal applies to the restoration of grazing function is untested. We identify gaps in our knowledge of best practices for the restoration of grazing function on coral reefs and conclude with some practical guidance on the establishment of targets for macroalgal reduction, along with strategic advice on grazer stocking in a given reef habitat.

Qualities Preceptors Prefer in a Dietetic Intern - W. Koszewski; C. Butler; M. Doyle; A. Wise; S. Nielsen (Journal of the Academy of Nutrition and Dietetics, 2023)

Forecasting suitable areas for wind turbine occurrence to proactively improve wildlife conservation - Matthew A. Boggie; Matthew J. Butler; Steven E. Sesnie; Brian A. Millsap; David R. Stewart; Grant M. Harris; James C. Broska (Journal for Nature Conservation, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Data on vegetation across forest edges from the FERN ( F orest E dge R esearch N etwork) - Karen A. Harper; Logan Gray; S. Ellen Macdonald; Daniel Lesieur; Danielle DeFields; Pavel Dodonov; Caroline Mary Adrianne Franklin; Sean R. Haughian; Liliana Mascarúa López; Alexandra Heathcote; Krista Jager; Renee Yang; et al. (Ecology, 2023)
Many studies have focused on vegetation across forest edges to study impacts of edges created by human activities on forest structure and composition, or patterns of vegetation at inherent natural edges. Our objective was to create a database of plant‐related variables across different types of edges from various studies (mainly from across Canada, but also in Brazil and Belize) to facilitate edge research. We compiled data on vegetation along more than 300 transects perpendicular to forest edges adjacent to clear‐cuts, burned areas, bogs, lakes, barrens, insect disturbances, and riparian areas from 24 studies conducted over the past three decades. Data were compiled for more than 400 plant species and forest structure variables (e.g., trees, logs, canopy cover). All data were collected with a similar sampling design of quadrats along transects perpendicular to forest edges, but with varying numbers of transects and quadrats, and distances from the edge. The purpose for most of the studies was either to determine the distance of edge influence (edge width) or to explore the pattern of vegetation along the edge to interior gradient. We provide data tables for the cover of plant species and functional groups, the species and size of live and dead trees, the density of saplings, maximum height of functional groups and shrub species, and the cover of functional groups at different heights (vertical distribution of vegetation). The Forest Edge Research Network (FERN) database provides extensive data on many variables that can be used for further study including meta‐analyses and can assist in answering questions important to conservation efforts (e.g., how is distance of edge influence from created edges affected by different factors?). We plan to expand this database with subsequent studies from the authors and we invite others to contribute to make this a more global database. The data are released under a CC0 license. When using these data, we ask that you cite this data paper and any relevant publications listed in our metadata file. We also encourage you to contact the first author if you are planning to use or contribute to this database.

Integrating management of marine activities in Australia - Robert L. Stephenson; Alistair J. Hobday; Ian Butler; Toni Cannard; Mel Cowlishaw; Ian Cresswell; Christopher Cvitanovic; Jon C. Day; Kirstin Dobbs; Leo X.C. Dutra; Stewart Frusher; Maree Fudge; et al. (Ocean & Coastal Management, 2023)

Developing a mealybug pheromone monitoring tool to enhance IPM practices in New Zealand vineyards - Nicola J. Sullivan; Vaughn A. Bell; Ruth C. Butler; Roger Wallis; Remya Ramesh; D. Srinivasa Reddy; Andrew M. Twidle; Barry Bunn; C. Rikard Unelius; Lee-Anne M. Manning; David M. Suckling (Journal of Pest Science, 2023)
Mealybugs are phloem-feeding insects found on many crops worldwide. In New Zealand vineyards, they transmit the economically important Grapevine leafroll-associated virus 3 (GLRaV-3). For some mealybug species, synthetic sex pheromones have been commercialised, and are used as monitoring tools. The mealybugs Pseudococcus longispinus and Pseudococcus calceolariae are major pests in many New Zealand vineyards. We present work on the development of a combined P. longispinus and P. calceolariae pheromone lure. The optimal dose for monitoring P. longispinus was found to be 10 µg of the ( S )-(+)-enantiomer, either alone or in the racemic mixture. Addition of the corresponding alcohol did not improve trap catch of P. longispinus . Both the P. longispinus and the P. calceolariae pheromone lures remained active in the field for 90 days. Combining the 2 species’ pheromones had no negative effects on male mealybug trap catch for either species. We conclude that the pheromone ester alone is the best lure for the male P. longispinus . Combining the two mealybug species’ pheromones into a single lure provides the New Zealand viticultural industry with an efficient monitoring tool. Late-vintage deployment of baited lures will provide information on mealybug abundance and local distribution that will inform the scope of future insecticide programmes, to target areas based on need rather than an area-wide application by default.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

The emergence of marine recreational drone fishing: Regional trends and emerging concerns - Alexander C. Winkler; Edward C. Butler; Colin G. Attwood; Bruce Q. Mann; Warren M. Potts (Ambio, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

Negative Food Effect of Danirixin: Use of PBPK Modelling to Explore the Effect of Formulation and Meal Type on Clinical PK - Richard S. Lloyd; Martin I. Hingle; Jackie C. Bloomer; Stephen J. Charles; James M. Butler; Alan Paul; Xiaofeng Zhu; Bruce Miller; Donald D’Amico; Alison Donald; Ruth Tal-Singer; Claire Ambery (Pharmaceutical Research, 2020)

Contrasting Futures for Australia’s Fisheries Stocks Under IPCC RCP8.5 Emissions – A Multi-Ecosystem Model Approach - Heidi R. Pethybridge; Elizabeth A. Fulton; Alistair J. Hobday; Julia Blanchard; Catherine M. Bulman; Ian R. Butler; William W. L. Cheung; Leo X. C. Dutra; Rebecca Gorton; Trevor Hutton; Richard Matear; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2020)

Using genetics to inform restoration and predict resilience in declining populations of a keystone marine sponge - Sarah M. Griffiths; Evelyn D. Taylor-Cox; Donald C. Behringer; Mark J. Butler; Richard F. Preziosi (Biodiversity and Conservation, 2020)
Genetic tools can have a key role in informing conservation management of declining populations. Genetic diversity is an important determinant of population fitness and resilience, and can require careful management to ensure sufficient variation is present. In addition, population genetics data reveal patterns of connectivity and gene flow between locations, enabling mangers to predict recovery and resilience, identify areas of local adaptation, and generate restoration plans. Here, we demonstrate a conservation genetics approach to inform restoration and management of the loggerhead sponge ( Spheciospongia vesparium ) in the Florida Keys, USA. This species is a dominant, habitat-forming component of marine ecosystems in the Caribbean region, but in Florida has suffered numerous mass mortality events. We developed microsatellite markers and used them to genotype sponges from 14 locations in Florida and a site each in The Bahamas, Belize and Barbuda. We found that genetic diversity levels were similar across all sites, but inbreeding and bottleneck signatures were present in Florida. Populations are highly structured at the regional scale, whilst within Florida connectivity is present in a weak isolation by distance pattern, coupled with chaotic genetic patchiness. Evidence of a weak barrier to gene flow was found in Florida among sites situated on opposite sides of the islands in the Middle Keys. Loggerhead sponge populations in Florida are vulnerable in the face of mass mortalities due to low connectivity with other areas in the region, as well as distance-limited and unpredictable local connectivity patterns. However, our discovery of Florida’s high genetic diversity increases hope for resilience to future perturbations. These results provide valuable insight for sponge restoration practice in Florida.

The multi-element stoichiometry of wet eucalypt forest is transformed by recent, frequent fire - Orpheus M. Butler; James J. Elser; Tom Lewis; Sarah C. Maunsell; Mehran Rezaei Rashti; Chengrong Chen (Plant and Soil, 2020)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

The stoichiometric legacy of fire regime regulates the roles of micro‐organisms and invertebrates in decomposition - Orpheus M. Butler; Tom Lewis; Mehran Rezaei Rashti; Sarah C. Maunsell; James J. Elser; Chengrong Chen (Ecology, 2019)
Decadal‐scale increases in fire frequency have the potential to deplete ecosystems of essential nutrients and consequently impede nutrient‐limited biological processes via stoichiometric imbalance. Decomposition, a fundamental ecosystem function and strong driver of future fire occurrence, is highly sensitive to nutrient availability and is, therefore, particularly important in this context. Here we show that 40 yr of quadrennial (4yB) and biennial (2yB) prescribed burning result in severely P‐ and N‐depleted litter stoichiometry, respectively, relative to fire exclusion. These effects exacerbated the nutrient limitation of microbial activities, constraining litter decomposition by 42.1% (4yB) and 23.6% (2yB) relative to unburned areas. However, invertebrate‐driven decomposition largely compensated for the diminished capacity of micro‐organisms under 4yB, suggesting that invertebrates could have an important stabilizing influence in fire‐affected ecosystems. This effect was strongly positively coupled with the strength of microbial P‐limitation and was not obviously or directly driven by fire regime‐induced changes in invertebrate community assemblage. Together, our results reveal that high‐frequency fire regimes promote nutrient‐poor, carbon‐rich ecosystem stoichiometry and, in doing so, disrupt ecosystem processes and modify the relative functionality of micro‐organisms and invertebrates.

Development of a quantitative PCR method for screening ichthyoplankton samples for bigheaded carps - Andrea K. Fritts; Brent C. Knights; James H. Larson; Jon J. Amberg; Christopher M. Merkes; Tariq Tajjioui; Steven E. Butler; Matthew J. Diana; David H. Wahl; Michael J. Weber; John D. Waters (Biological Invasions, 2019)

Advances in Mechanistic Approaches to Quantifying Biophysical Fire Effects - J. J. O’Brien; J. K. Hiers; J. M. Varner; C. M. Hoffman; M. B. Dickinson; S. T. Michaletz; E. L. Loudermilk; B. W. Butler (Current Forestry Reports, 2018)

Analytical performance of a platform for point-of-care CRP testing in adults consulting for lower respiratory tract infection in primary care - Veerle Matheeussen; Viviane Van Hoof; Katherine Loens; Christine Lammens; Anouk Vanderstraeten; Samuel Coenen; Chris C. Butler; Paul Little; Theo J. M. Verheij; Herman Goossens; Margareta Ieven (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Evidence for protandry in Polydactylus quadrifilis in the Kwanza Estuary, Angola, and its implications for local fisheries - Edward C. Butler; Amber-Robyn Childs; Alexander C. Winkler; Marianne V. Milner; Warren M. Potts (Environmental Biology of Fishes, 2018)

A Novel Aza-MBP Altered Peptide Ligand for the Treatment of Experimental Autoimmune Encephalomyelitis - Nicole N. M. Trager; Jonathan T. Butler; Jennifer Harmon; Joshua Mount; Maria Podbielska; Azizul Haque; Naren L. Banik; Craig C. Beeson (Molecular Neurobiology, 2018)

Rate of decline of Gaeumannomyces graminis var. tritici inoculum and decomposition of residues from wheat cultivars - R. F. van Toor; R. C. Butler; M. G. Cromey (Australasian Plant Pathology, 2018)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Wheat cultivar susceptibility to Gaeumannomyces graminis var. tritici and influence on Pseudomonas fluorescence numbers in the rhizosphere - R. F. van Toor; S. Chng; R. M. Warren; R. C. Butler; M. G. Cromey; R. A. Craigie; B. L. McCloy (Australasian Plant Pathology, 2016)

Using a model based fourth-corner analysis to explain vegetation change following an extraordinary fire disturbance - S. E. Venn; C. M. Pickering; S. A. Butler; A. D. Letten (Oecologia, 2016)

Reconstructing global overturning from meridional density gradients - E. D. Butler; K. I. C. Oliver; J. J.-M. Hirschi; J. V. Mecking (Climate Dynamics, 2016)

Molecular and morphological insights into the origin of the invasive greater white-toothed shrew (Crocidura russula) in Ireland - Laura M. Gargan; Raphaël Cornette; Jon M. Yearsley; W. Ian Montgomery; Joana Paupério; Paulo C. Alves; Fidelma Butler; Michel Pascal; Anne Tresset; Anthony Herrel; John Lusby; David G. Tosh; et al. (Biological Invasions, 2016)

2nd International Conference on Progressive Multifocal Leukoencephalopathy (PML) 2015: JCV virology, progressive multifocal leukoencephalopathy pathogenesis, diagnosis and risk stratification, and new approaches to prevention and treatment - Andriani C. Patera; Scott L. Butler; Paola Cinque; David B. Clifford; Robert Elston; Robert L. Garcea; Eugene O. Major; Dejan Pavlovic; Ilse S. Peterson; Anne M. Ryan; Kenneth L. Tyler; Thomas Weber (Journal of NeuroVirology, 2015)

Quantitative PCR to detect Gaeumannomyces graminis var. tritici in symptomatic and non-symptomatic wheat roots - S. Keenan; M. G. Cromey; S. A. Harrow; S. L. Bithell; R. C. Butler; S. S. Beard; A. R. Pitman (Australasian Plant Pathology, 2015)

Mobilization of horizontally acquired island 2 is induced in planta in the phytopathogen P ectobacterium atrosepticum SCRI 1043 and involves the putative relaxase ECA 0613 and quorum sensing - Bhanupratap R. Vanga; Pavithra Ramakrishnan; Ruth C. Butler; Ian K. Toth; Clive W. Ronson; Jeanne M. E. Jacobs; Andrew R. Pitman (Environmental Microbiology, 2015)
Summary Integrative and conjugative elements ( ICEs ) contribute to the rapid evolution of bacterial pathogens via horizontal gene transfer of virulence determinants. ICEs have common mechanisms for transmission, yet the cues triggering this process under natural environmental or physiological conditions are largely unknown. In this study, mobilization of the putative ICE horizontally acquired island 2 ( HAI 2), present in the chromosome of the phytopathogen P ectobacterium atrosepticum SCRI 1043, was examined during infection of the host plant potato. Under these conditions, mobilization of HAI 2 increased markedly compared with in vitro cultures. In planta ‐induced mobilization of HAI 2 was regulated by quorum sensing and involved the putative ICE ‐encoded relaxase ECA 0613. Disruption of ECA 0613 also reduced transcription of genes involved in production of coronafacic acid (Cfa), the major virulence factor harboured on HAI 2, whereas their expression was unaffected in the quorum‐sensing ( expI ) mutant. Thus, suppression of cfa gene expression was not regulated by the mobilization of the ICE per se , but was due directly to inactivation of the relaxase. The identification of genetic factors associated solely with in planta mobilization of an ICE demonstrates that this process is highly adapted to the natural environment of the bacterial host and can influence the expression of virulence determinants.

Analytic laboratory performance of a point of care urine culture kit for diagnosis and antibiotic susceptibility testing - E. Bongard; N. Frimodt-Møller; M. Gal; M. Wootton; R. Howe; N. Francis; H. Goossens; C. C. Butler (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

A missense variant in CST3 exerts a recessive effect on susceptibility to age-related macular degeneration resembling its association with Alzheimer’s disease - Joe M. Butler; Umar Sharif; Manir Ali; Martin McKibbin; Joseph P. Thompson; Richard Gale; Yit C. Yang; Chris Inglehearn; Luminita Paraoan (Human Genetics, 2015)

Resistance to Spongospora subterranea induced in potato by the elicitor β-aminobutyric acid - M. Loreto Hernandez Maldonado; Richard E. Falloon; Ruth C. Butler; Anthony J. Conner; Simon R. Bulman (Australasian Plant Pathology, 2015)

The influence of growth stage of different cereal species on host susceptibility to Gaeumannomyces graminis var. tritici and on Pseudomonas populations in the rhizosphere - R. F. van Toor; S. F. Chng; R. M. Warren; R. C. Butler; M. G. Cromey (Australasian Plant Pathology, 2015)

Atlantic bluefin tuna Thunnus thynnus feeding ecology in the northern Gulf of Mexico: a preliminary description of diet from the western Atlantic spawning grounds - C. M. Butler; J. M. Logan; J. M. Provaznik; E. R. Hoffmayer; M. D. Staudinger; J. M. Quattro; M. A. Roberts; G. W. Ingram; A. G. Pollack; M. E. Lutcavage (Journal of Fish Biology, 2015)
A combination of stomach contents, nitrogen stable‐isotope and tissue C:N values are presented to demonstrate feeding activity of Atlantic bluefin tuna Thunnus thynnus on the Gulf of Mexico (GOMEX) spawning grounds. Diets include teleosts, cephalopods, crustaceans and a pelagic tunicate ( Pyrosoma atlanticum ). Results reveal the need to classify the GOMEX as a T. thynnus feeding ground.

Agronomic factors affect powdery scab of potato and amounts of Spongospora subterranea DNA in soil - Farhat A. Shah; Richard E. Falloon; Ruth C. Butler; Ros A. Lister; Steve M. Thomas; Denis Curtin (Australasian Plant Pathology, 2014)

Light brown apple moth (Epiphyas postvittana) (Lepidoptera: Tortricidae) colonization of California - D. M. Suckling; L. D. Stringer; D. B. Baird; R. C. Butler; T. E. S. Sullivan; D. R. Lance; G. S. Simmons (Biological Invasions, 2014)

Application of stable isotope mixing models for defining trophic biomagnification pathways of mercury and selenium - H. J. Jones; K. M. Swadling; E. C. V. Butler; L. A. Barry; C. K. Macleod (Limnology and Oceanography, 2014)
Trophic models based on nitrogen stable isotope ratios ( δ 15 N) have been shown to predict changes in mercury (Hg) concentrations in fish; however, they are usually applied at the ecosystem scale and are rarely directed at known trophic pathways. We discuss a novel approach in which we combined gut contents analysis and stable isotope analyses ( δ 15 N and δ 13 C) into a Bayesian isotopic mixing model to provide a quantitative estimate of Hg and selenium (Se) biomagnification in an estuarine food web. Estimates of the relationship between total mercury (THg) and methylmercury (MeHg) were significantly improved in mixing model‐adjusted food webs over models that included all known prey sources. Spatial differences in dietary composition and MeHg bioavailability offer strong evidence that local food webs can have a significant effect on the biomagnification of Hg within benthic fish species. While no evidence of Se biomagnification was found, lower Se : Hg ratios at higher trophic levels could be attributed to increasing trophic Hg concentration. Furthermore, stable isotope analysis suggested Hg and Se biotransfer from benthic sources to fish. Overall, the findings highlight that isotope mixing models can be a significant aid in assessments of contaminant biomagnification, particularly when it is important to define food pathways to top predators.

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Recent environmental change and trace metal pollution in World Heritage Bathurst Harbour, southwest Tasmania, Australia - Krystyna M. Saunders; Jennifer J. Harrison; Edward C. V. Butler; Dominic A. Hodgson; Andrew McMinn (Journal of Paleolimnology, 2013)

Are the teleconnections of Central Pacific and Eastern Pacific El Niño distinct in boreal wintertime? - C. I. Garfinkel; M. M. Hurwitz; D. W. Waugh; A. H. Butler (Climate Dynamics, 2013)

Sources of Botrytis cinerea inoculum for flower infection in blackcurrants in New Zealand - K. Boyd-Wilson; F. Obanor; R. C. Butler; P. Harris-Virgin; G. I. Langford; J. T. Smith; M. Walter (Australasian Plant Pathology, 2013)

Effects of different rates of Gaeumannomyces graminis var. tritici inoculum for detecting take-all suppression in soils - S. F. Chng; A. Stewart; M. G. Cromey; S. L. Dodd; R. C. Butler; M. V. Jaspers (Australasian Plant Pathology, 2013)

Methanogenic potential of Arctic and Antarctic subglacial environments with contrasting organic carbon sources - Marek Stibal; Jemma L. Wadham; Grzegorz P. Lis; Jon Telling; Richard D. Pancost; Ashley Dubnick; Martin J. Sharp; Emily C. Lawson; Catriona E. H. Butler; Fariha Hasan; Martyn Tranter; Alexandre M. Anesio (Global Change Biology, 2012)
Subglacial environments are largely anoxic, contain organic carbon ( OC ) overridden by glacier ice during periods of advance, and harbour active microbial communities. This creates favourable conditions for OC degradation via methanogenesis. It has been hypothesized that OC beneath ice sheets is converted to methane ( CH 4 ) and may be released to the atmosphere during retreat. However, there are limited data available to support this contention. Here, we present new data on the abundance, diversity and activity of methanogenic archaea and the amount and character of OC in subglacial sediments from Arctic and Antarctic glacial systems based on different substrate types. We employed long‐term laboratory incubations to quantify the CH 4 production potential in different subglacial settings. Significant numbers of methanogens (up to 7 × 10 4 cells g −1 ) were detected in the samples and clones of Methanomicrobiales and Methanosarcinales were identified in clone libraries. Long lag periods (up to >200 days) were observed before significant CH 4 concentrations were measured. We report order of magnitude differences in rates of CH 4 production (10 1 –10 5 fmol g −1 d −1 ) in different subglacial sediments, reflecting contrasts in the origin of the sediment and the OC character. Hence, we predict that contrasting rates of CH 4 production are likely to occur beneath glaciers and ice sheets that overran different types of substrate. We subsequently estimated the potential for CH 4 production beneath the Laurentide/Inuitian/Cordilleran and Fennoscandian Ice Sheets during a typical 85 ka Quaternary glacial/interglacial cycle. CH 4 production from lacustrine‐derived OC is likely to be an order of magnitude higher (~6.3–27 Pg C) than that from overridden soils (~0.55–0.68 Pg C), possibly due to a difference in lability between lacustrine and soil OC . While representing a fraction of the entire OC pool (~418–610 Pg C), this finding highlights the importance of considering the character of different OC pools when calculating subglacial CH 4 production.

Green and black tea intake in relation to prostate cancer risk among Singapore Chinese - Julia A. Montague; Lesley M. Butler; Anna H. Wu; Jeanine M. Genkinger; Woon-Puay Koh; Alvin S. Wong; Renwei Wang; Jian-Min Yuan; Mimi C. Yu (Cancer Causes & Control, 2012)

Response of Female Frankliniella occidentalis (Pergande) to Visual Cues and Para-anisaldehyde in a Flight Chamber - Melanie M. Davidson; Ruth C. Butler; David A. J. Teulon (Journal of Insect Behavior, 2012)

Relative humidity at Armagh Observatory, 1838–2008 - C. J. Butler; A. M. García‐Suárez (International Journal of Climatology, 2012)
We present a calibrated atmospheric humidity series for Armagh Observatory, Northern Ireland. Beginning in 1838 and continuing to the present day, this series is believed to be the longest presented so far. Daily wet‐bulb and dry‐bulb temperature readings are corrected for the time of reading and for known instrumental errors to determine mean monthly, seasonal and annual relative humidity (RH) at 09:00 GMT from 1838 to 2008 and at 21:00 GMT from 1844 to 1964. The mean seasonal and annual time series of RH at this site show only marginal evidence for a trend in RH since the 1880s, however, there is significant decadal and multi‐decadal variability, some of which appears to be cyclic. Wavelet analysis indicates the presence of two quasi‐periodic components in RH, one ranging from 23.4 to 25.5 years and the other from 36 to 51 years. We discuss potential physical origins of these cycles such as changes in the atmospheric and thermohaline circulation and the solar magnetic cycle. There is a small but significant anti‐correlation between RH and northerly winds. Two conspicuous peaks in RH during the 19th century coincide with major infestations of potato blight in Ireland. Copyright © 2011 Royal Meteorological Society

Soil warming alters nitrogen cycling in a New England forest: implications for ecosystem function and structure - S. M. Butler; J. M. Melillo; J. E. Johnson; J. Mohan; P. A. Steudler; H. Lux; E. Burrows; R. M. Smith; C. L. Vario; L. Scott; T. D. Hill; N. Aponte; et al. (Oecologia, 2012)

Nest box design for the study of diurnal raptors and owls is still an overlooked point in ecological, evolutionary and conservation studies: a review - Marcel M. Lambrechts; Karen L. Wiebe; Peter Sunde; Tapio Solonen; Fabrizio Sergio; Alexandre Roulin; Anders Pape Møller; Bernat C. López; Juan A. Fargallo; Klaus-Michael Exo; Giacomo Dell’Omo; David Costantini; et al. (Journal of Ornithology, 2012)

Generation of antibody- and B cell-deficient pigs by targeted disruption of the J-region gene segment of the heavy chain locus - M. Mendicino; J. Ramsoondar; C. Phelps; T. Vaught; S. Ball; T. LeRoith; J. Monahan; S. Chen; A. Dandro; J. Boone; P. Jobst; A. Vance; et al. (Transgenic Research, 2011)

Targeted disruption of the porcine immunoglobulin kappa light chain locus - J. Ramsoondar; M. Mendicino; C. Phelps; T. Vaught; S. Ball; J. Monahan; S. Chen; A. Dandro; J. Boone; P. Jobst; A. Vance; N. Wertz; et al. (Transgenic Research, 2011)

Recommendation of short tandem repeat profiling for authenticating human cell lines, stem cells, and tissues - Rita Barallon; Steven R. Bauer; John Butler; Amanda Capes-Davis; Wilhelm G. Dirks; Eugene Elmore; Manohar Furtado; Margaret C. Kline; Arihiro Kohara; Georgyi V. Los; Roderick A. F. MacLeod; John R. W. Masters; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

Cigarette smoking and risk of prostate cancer among Singapore Chinese - Lesley M. Butler; Renwei Wang; Alvin S. Wong; Woon-Puay Koh; Mimi C. Yu (Cancer Causes & Control, 2009)

Thinking and managing outside the box: coalescing connectivity networks to build region-wide resilience in coral reef ecosystems - R. S. Steneck; C. B. Paris; S. N. Arnold; M. C. Ablan-Lagman; A. C. Alcala; M. J. Butler; L. J. McCook; G. R. Russ; P. F. Sale (Coral Reefs, 2009)

Metallothionein Treatment Attenuates Microglial Activation and Expression of Neurotoxic Quinolinic Acid Following Traumatic Brain Injury - R. S. Chung; Y. K. Leung; C. W. Butler; Y. Chen; E. D. Eaton; M. W. Pankhurst; A. K. West; G. J. Guillemin (Neurotoxicity Research, 2009)

A Greenhouse Assay for Powdery Scab (Spongospora subterranea f. sp. subterranea) Resistance in Potato - S. J. Baldwin; R. A. Genet; R. C. Butler; J. M. E. Jacobs (Potato Research, 2008)

Dinosaur remains from the La Quinta Formation (Lower or Middle Jurassic) of the Venezuelan Andes - Paul M. Barrett; Richard J. Butler; Scott C. Moore-Fay; Fernando E. Novas; John M. Moody; James M. Clark; Marcelo R. Sänchez-Villagra (PalZ, 2008)

Transgenic Potato Lines Expressing cry1Ba1 or cry1Ca5 Genes are Resistant to Potato Tuber Moth - S. Meiyalaghan; J. M. E. Jacobs; R. C. Butler; S. D. Wratten; A. J. Conner (Potato Research, 2007)

Soil temperatures at Armagh Observatory, Northern Ireland, from 1904 to 2002 - A. M. García-Suárez; C. J. Butler (International Journal of Climatology, 2006)

Expression of cry1Ac9 and cry9Aa2 genes under a potato light-inducible Lhca3 promoter in transgenic potatoes for tuber moth resistance - Sathiyamoorthy Meiyalaghan; Jeanne M. E. Jacobs; Ruth C. Butler; Steve D. Wratten; Anthony J. Conner (Euphytica, 2006)

Air temperatures at Armagh Observatory, Northern Ireland, from 1796 to 2002 - C. J. Butler; A. M. García Suárez; A. D. S. Coughlin; C. Morrell (International Journal of Climatology, 2005)
Three independent mean temperature series for Armagh Observatory, covering the period 1796–2002 have been calibrated and corrected for the time of reading and exposure. Agreement between the three series is good in regions of overlap. With a short gap in the Armagh data from 1825 to 1833 filled by data from two stations in Dublin, the resulting series is the longest for the island of Ireland and one of the longest for any single site in the British Isles. Over the past 207 years, we note that temperatures in Armagh, in all seasons, show a gradual overall trend upwards. However, there are seasonal differences: summer and spring temperatures have increased by only half as much as those in autumn and winter. This is partly due to the exceptionally cold winters and autumns experienced prior to 1820. Relative to the overall trend, warm periods occurred in Ireland, as in other parts of Europe, in the mid‐19th century, in the mid‐20th century and at the end of the 20th century. Relatively cool temperatures prevailed in the early 19th century, in the 1880s and in the 1970s. Thus, if the baseline against which current temperatures are compared were moved from the late 19th century to include the earlier warm period, the apparent warming at the end of the late 20th century would be correspondingly reduced. A gradual decline in the daily temperature range at Armagh since 1844 may have resulted from higher minimum temperatures associated with increased cloudiness. A 7.8 year periodicity is identified in winter and spring mean temperatures at Armagh, which is probably a consequence of the North Atlantic oscillation. Copyright © 2005 Royal Meteorological Society

Assessment of genetic diversity in isolates of Ciborinia camelliae Kohn from New Zealand and the United States of America - R. F. van Toor; H. J. Ridgway; R. C. Butler; M. V. Jaspers; A. Stewart (Australasian Plant Pathology, 2005)

Accuracy, efficiency and robustness of four algorithms allowing full sibship reconstruction from DNA marker data - K. Butler; C. Field; C. M. Herbinger; B. R. Smith (Molecular Ecology, 2004)
In the problem of reconstructing full sib pedigrees from DNA marker data, three existing algorithms and one new algorithm are compared in terms of accuracy, efficiency and robustness using real and simulated data sets. An algorithm based on the exclusion principle and another based on a maximization of the Simpson index were very accurate at reconstructing data sets comprising a few large families but had problems with data sets with limited family structure, while a Markov Chain Monte Carlo (MCMC) algorithm based on the maximization of a partition score had the opposite behaviour. An MCMC algorithm based on maximizing the full joint likelihood performed best in small data sets comprising several medium‐sized families but did not work well under most other conditions. It appears that the likelihood surface may be rough and presents challenges for the MCMC algorithm to find the global maximum. This likelihood algorithm also exhibited problems in reconstructing large family groups, due possibly to limits in computational precision. The accuracy of each algorithm improved with an increasing amount of information in the data set, and was very high with eight loci with eight alleles each. All four algorithms were quite robust to deviation from an idealized uniform allelic distribution, to departures from idealized Mendelian inheritance in simulated data sets and to the presence of null alleles. In contrast, none of the algorithms were very robust to the probable presence of error/mutation in the data. Depending upon the type of mutation or errors and the algorithm used, between 70 and 98% of the affected individuals were classified improperly on average.

Chemically-Enhanced Phytoextraction of Cadmium-Contaminated Soils Using Wheat (Triticum aestivumL.) - M. T. Begonia; G. B. Begonia; A. D. Butler; U. Griffin; C. Young (Bulletin of Environmental Contamination and Toxicology, 2003)

A direct regional scale estimate of transgene movement from genetically modified oilseed rape to its wild progenitors - M. J. Wilkinson; I. J. Davenport; Y. M. Charters; A. E. Jones; J. Allainguillaume; H. T. Butler; D. C. Mason; A. F. Raybould (Molecular Ecology, 2000)
One of the major environmental concerns over genetically modified (GM) crops relates to transgene movement into wild relatives. The pattern of hybridization ultimately affects the scale and rapidity of ecological change and the feasibility of containment. A new procedure for quantifying hybrid formation over large areas is described. Remote sensing was used to identify possible sites of sympatry between Brassica napus and its progenitor species across 15 000 km 2 of south‐east England in 1998. Two sympatric populations with B. rapa and one with B. oleracea were found over the entire survey area. Every newly recruited plant in these populations in 1999 was screened for hybrid status using flow cytometry and molecular analyses. One hybrid was observed from the 505 plants screened in the B. rapa populations but none of the nine B. oleracea recruits were hybrids. Measures to minimize gene flow are suggested, and a procedure for the post‐release evaluation and containment of GM cultivars is proposed.

Identification of genomic regions associated with stay green in sorghum by testing RILs in multiple environments - Y. Z. Tao; R. G. Henzell; D. R. Jordan; D. G. Butler; A. M. Kelly; C. L. McIntyre (Theoretical and Applied Genetics, 2000)

Menstrual risk factors and early-onset breast cancer - Lesley M. Butler; Nancy A. Potischman; Beth Newman; Robert C. Millikan; Donna Brogan; Marilie D. Gammon; Christine A. Swanson; Louise A. Brinton (Cancer Causes & Control, 2000)

The β enolase subunit displays three different patterns of microheterogeneity in human striated muscle - T. Merkulova; L-E. Thornell; G. Butler-Browne; C. Oberlin; M. Lucas; N. Lamandé; M. Lazar; A. Keller (Journal of Muscle Research and Cell Motility, 1999)

Regional distribution of metallothionein and zinc in the mouse gut - C. D. Tran; R. N. Butler; J. C. Philcox; A. M. Rofe; G. S. Howarth; P. Coyle (Biological Trace Element Research, 1998)

Effect of contraction strength on responses in biceps brachii and adductor pollicis to transcranial magnetic stimulation - J. L. Taylor; Gabrielle M. Allen; Jane E. Butler; S. C. Gandevia (Experimental Brain Research, 1997)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

Temporal patterns and transport processes in recruitment of spiny lobster ( Panulirus argus ) postlarvae to south Florida - C. A. Acosta; T. R. Matthews; M. J. Butler IV. (Marine Biology, 1997)

The effect of thyroid hormones on the aerobic development of locomotor and cardiac muscles in the barnacle goose - K. E. Deaton; C. M. Bishop; P. J. Butler (Journal of Comparative Physiology B, 1997)

Some properties of adenylate kinase from chemolithotrophically grown Thiobacillus novellus - I. R. C. McKellar; A. M. Charles; B. J. Butler (Archives of Microbiology, 1980)

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)

Preliminary seed certification notes - E. R. Dykeman; C. H. Hadley; W. A. McCubbin; Harold L. Bailey; O Butler; M. F. Barrus; R. F. Payne; N. W. Glimes; H. O. Werner; W. Stuart; Donald Folsom; W. H. M. (American Journal of Potato Research, 1923)